2011
DOI: 10.1111/j.1365-2052.2011.02251.x
|View full text |Cite
|
Sign up to set email alerts
|

Identifying putative candidate genes and pathways involved in immune responses to porcine reproductive and respiratory syndrome virus (PRRSV) infection

Abstract: Differences in gene expression were compared between RNAs from lungs of high (HR) and low (LR) porcine reproductive and respiratory syndrome virus (PRRSV) burden pigs using the swine protein-annotated long oligonucleotide microarray, the Pigoligoarray. Pathway analyses were carried out to determine biological processes, pathways and networks that differ between the LR and HR responses. Differences existed between HR and LR pigs for 16 signalling pathways [P < 0.01/-log (P-value) >1.96]. Top canonical pathways … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 33 publications
(46 reference statements)
4
32
0
Order By: Relevance
“…PPP2R1A (serine/threonine-protein phosphatase regulatory subunit A) contributes to regulation of cell autophagy as part of an anti-bacterial response [129], and is involved in T lymphocytes signaling processes throughout porcine respiratory syndrome virus infection (rev. by [130]). These results suggest that presumably “salinity” - affected outliers, identified by the design 4, might also be due to population differences in response to G. salaris .…”
Section: Discussionmentioning
confidence: 91%
“…PPP2R1A (serine/threonine-protein phosphatase regulatory subunit A) contributes to regulation of cell autophagy as part of an anti-bacterial response [129], and is involved in T lymphocytes signaling processes throughout porcine respiratory syndrome virus infection (rev. by [130]). These results suggest that presumably “salinity” - affected outliers, identified by the design 4, might also be due to population differences in response to G. salaris .…”
Section: Discussionmentioning
confidence: 91%
“…Second, we used a blocked reference design (Steibel and Rosa, 2005). In contrast to common reference designs (Bates et al, 2008; Xiao et al, 2010a,b; Wysocki et al, 2012), our design allowed us to use 0 DPI samples as a reference, and still include 0 DPI in tests, which was instrumental in assessing baseline effects before infection. Additionally, because of the design used to accommodate single cDNA samples, this study has the flexibility of incorporating future data for differential expression analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, differential expression of a reduced number of immune related genes has been evaluated (Petry et al, 2007; Lunney et al, 2010) and global differential expression has been assessed in vivo (Bates et al, 2008; Xiao et al, 2010a,b; Zhou et al, 2011; Wysocki et al, 2012) and in vitro (Lee et al, 2004a,b; Miller and Fox, 2004; Genini et al, 2008; Ait-Ali et al, 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the TAP1 gene has been studied as one effective functional gene for disease resistance in pigs [6,7]. Wysocki [8] et al found the TAP1 gene up-regulated in lung tissue when pig infected by porcine reproductive and respiratory syndrome virus (PRRSV). Uthe et al [9] found the TAP1 gene might play an important role in Salmonella resistance.…”
Section: Introductionmentioning
confidence: 99%